Potret Kekerasan Terhadap Kaum Perempuan Yang Terjadi Di Dalam Novel “A Beautiful Mistake” Karya Saviana Jose - Irma Yunita Sukriadi (PIKTORIAL : Journal of Humanities, 2021)
This research is aimed at: 1) Describe the shape and function of employee direct speech with customers at Pronto Moda Bintaro, and 2) Describe the shape and function of indirect speech employees with customers at Pronto Moda Bintaro. Theoretical guidelines used to analyze data related ti direct speech and indirect speech from Wijana and Rohmadi and Nadar. The study uses qualitative descriptive research methods. The object examined in this study is a reference between employees to customers at Pronto Moda Bintaro. Sampel data used by as many as 36 data and is obtained using a basic technique of reviewing, measuring, and logging in data collection. Based on analysis, the results have been found that in employees conversations with customers at Pronto Moda Bintaro there is a speech speech number 25 data that serves to ask 17 data, to command 4 data, and to tell 4 data, and indirect acts amount to 12 data that function to command. So the speech from found in employees conversation toward customers at Pronto Moda Bintaro usesa lot of direct speech number 25 data.